Ailanthus excelsa Roxb. : An agroforestry tree species for arid and semi-arid ecosystems - Kaushik, N.; Gaur, Ram Karan; Mehta, Kajal; Kumari, Sushil; Yadav, P.K. (Indian Journal of Agroforestry, 2020)
Rising population and urbanization, coupled with land degradation, soil salinization, and global warming are causing food insufficiency in large parts of World. The situation is more serious in tropical and sub-tropical areas. Integration of trees in the farming systems is one option to cope up with these problems Ailanthus excelsa is highly suited for agroforestry systems on degraded soils of arid and semi-arid agro-ecosystems to meet out the demand of human and cattle population without degradation of land and natural resources. This review indicated the potential of A. excelsa based farming systems to meet out the requirement of food, fodder, firewood and other products as well as resource conservation in arid and semi-arid regions. A case study from Chaudhary Charan Singh Haryana Agricultural University Regional Research Station, Bawal (Haryana) India showed that Rs. 38, 800/ha / year can be earned from block plantation of A. excelsa. The yield of some of the crops had decreased under the tree but production of fuel, fodder and raw material for industry and soil fertility enhancement and other ecological services as well as goods have compensated this loss. To use A. excelsa as a resource for supplying fodder, firewood and timber for rural population and carbon sequestration then research and development will have to play an important role in effective education, strengthening and creation of markets for timber and other products, the economic support price policies as in case of crops like wheat and rice, community lands and road avenues on sharing basis with farmers of adjoining areas as efforts made in different parts of world with other plant species, and addressing the research needs and policy for linking knowledge to action.